Lower extremity peripheral artery disease in the absence of traditional risk factors. The Multi-Ethnic Study of Atherosclerosis - Aboyans, Victor (Atherosclerosis, 2010)
OBJECTIVE: Lower-extremity peripheral artery disease (LE-PAD), is strongly related to traditional risk factors (smoking, hypertension, dyslipidemia, diabetes). We hypothesized that the prevalence of LE-PAD in the absence of traditional CVD risk factors is not negligible, and that this condition would remain associated with subclinical atherosclerosis in other territories. METHODS: In the Multi-Ethnic Study of Atherosclerosis, we classified participants without any traditional risk factor according to their ankle-brachial index (ABI) into 3 groups: low (<1.00), normal (1.00–1.30) and high (>1.30) ABI. Coronary or carotid artery diseases were defined by the presence of any coronary artery calcification (CAC score > 0) or carotid plaque, respectively. RESULTS: Among the 6814 participants, 1932 had no traditional risk factors. A low- and high ABI were found in 176 (9%) and 149 (7.8%) cases, respectively. Lower glomerular filtration rate (OR: 0.88/10 units, p = 0.04) and higher Interleukin-6 levels (OR: 1.42/natural-log unit, p = 0.02) were associated with low ABI. Past smoking (cessation > 10 years) and pulse pressure had borderline association with low ABI. In adjusted models, low-ABI was significantly associated with CAC prevalence (OR: 1.22, p < 0.03). No significant association was found with carotid plaque. CONCLUSION: In the absence of traditional CVD risk factors, LE-PAD is still common and associated with coronary artery disease.